Inpatient Facility Distribution and Primary Healthcare Centers Demand Based on Location-Quotient in Bali within 2015-2019 Period - Ni Made Hegard Sukmawati (Scopus ID: 57189732715) (Warmadewa University, 2021)
The study of access to primary healthcare centers (PHCs) in the middle region of Indonesia, including Bali, is scarce. A study on primary healthcare access is worth undertaken in this region because it is usually given less attention regarding its fair distribution of healthcare facilities in relation to their population. This study aimed at determining geographical distribution and concentration of PHCs facility and demand in Bali Province. This study focused on the inpatient facility and demand of PHCs in relation to population. Data of PHCs’ inpatient facility and demand of each regency/city and population data were obtained from Bali Health Profile of 2015 to 2019. Location quotients (LQ) of inpatient facility and inpatient demand for each regency/city were calculated to determine the spatial concentration of the two variables compared to the provincial average. Our study found that there was variation in facility and demand for inpatient care in PHCs in Bali. A low level of inpatient facility and demand was seen in Regency of Buleleng, Denpasar, and Gianyar, while a high level of facility and demand for inpatient facility was observed in Regency of Jembrana, Tabanan, Klungkung, and Karangasem. A unique finding was also noticed in Bangli Regency, where the inpatient facility of PHC was high, while the inpatient demand was low. This might indicate a need for evaluation of the inpatient facility of PHC in this Regency. Keywords: Access to healthcare, Bali, inpatient care, puskesmas, primary healthcare centers.